Reframing Perceptions in Restorative Dentistry: Evidence-Based Dentistry and Clinical Decision-Making - Ayah A Al-Asmar; Ahmad S Al-Hiyasat; Motasum Abu-Awwad; Hakam N Mousa; Nesreen A Salim; Waed Almadani; Furat Rihan; Faleh A Sawair; Nigel B Pitts (Hindawi Limited, 2021)
Objectives. The worldwide interest of both dentists and patients in esthetic dentistry has affected decision-making in dental practice. The aim of this study was to investigate contemporary dental practice in restorative dentistry and the relationship between evidence-based dentistry in caries research and decision-making in clinical practice in restorative dentistry. Methods. The study was conducted through a structured questionnaire distributed randomly at the Jordanian Dental Association registered dentists in Jordan. The questionnaire aimed to clarify the degree of knowledge and practice of evidence-based dentistry in caries research the dentists hold regarding clinical decision-making in restorative dentistry. Results. The majority of the surveyed dentists (77%) treat teeth with irreversible pulpitis with root canal treatment rather than vital pulp therapy. 13.8% routinely insert a post and 23% routinely crown the tooth after root canal treatment regardless of the remaining tooth structure. Badly damaged teeth are treated with full crowns in 72% of the cases. Regarding Hollywood smile or smile makeover, the majority of dentists choose conservative approaches, and implants were the first choice to replace missing teeth for 93.8% of the surveyed dentists. Conclusion. A higher degree of implementation of evidence-based dentistry in clinical decision-making was found in Prosthetic Dentistry than in Endodontics. Yet, the gap between evidence-based data and clinical practice needs bridging. More emphasis on communicating these data to educators to integrate them into the dental curriculum is a must.